2019
DOI: 10.5194/acp-19-6351-2019
|View full text |Cite
|
Sign up to set email alerts
|

Northern Hemisphere continental winter warming following the 1991 Mt. Pinatubo eruption: reconciling models and observations

Abstract: Abstract. It has been suggested, and is widely believed, that the anomalous surface warming observed over the Northern Hemisphere continents in the winter following the 1991 eruption of Mt. Pinatubo was, in fact, caused by that eruption, via a stratospheric pathway that involves a strengthening of the polar vortex. However, most studies that have examined multiple, state-of-the-art, coupled climate models report that, in the ensemble mean, the models do not show winter warming after the Mt. Pinatubo eruption. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
82
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(89 citation statements)
references
References 69 publications
6
82
1
Order By: Relevance
“…This has been previously attributed to a strengthening of the stratospheric polar vortex and associated positive phase of the North Atlantic Oscillation, bringing warmer air from the North Atlantic (Perlwitz & Graf, 1995;Robock, 2000;Robock & Mao, 1992;Zambri & Robock, 2016). This mechanism has recently been called into question owing to the importance of internal variability (Polvani et al, 2019); we have not isolated the mechanism for this warming in CESM, but note that it is a statistically robust feature of CESM climate. This may be due to the larger magnitude of Last Millennium eruptions relative to Pinatubo; the response appears notably stronger than that noted in Polvani et al (2019) for the larger Tropical eruptions.…”
Section: Atmospheric Response To Eruptionsmentioning
confidence: 87%
See 1 more Smart Citation
“…This has been previously attributed to a strengthening of the stratospheric polar vortex and associated positive phase of the North Atlantic Oscillation, bringing warmer air from the North Atlantic (Perlwitz & Graf, 1995;Robock, 2000;Robock & Mao, 1992;Zambri & Robock, 2016). This mechanism has recently been called into question owing to the importance of internal variability (Polvani et al, 2019); we have not isolated the mechanism for this warming in CESM, but note that it is a statistically robust feature of CESM climate. This may be due to the larger magnitude of Last Millennium eruptions relative to Pinatubo; the response appears notably stronger than that noted in Polvani et al (2019) for the larger Tropical eruptions.…”
Section: Atmospheric Response To Eruptionsmentioning
confidence: 87%
“…This mechanism has recently been called into question owing to the importance of internal variability (Polvani et al, 2019); we have not isolated the mechanism for this warming in CESM, but note that it is a statistically robust feature of CESM climate. This may be due to the larger magnitude of Last Millennium eruptions relative to Pinatubo; the response appears notably stronger than that noted in Polvani et al (2019) for the larger Tropical eruptions.…”
Section: Atmospheric Response To Eruptionsmentioning
confidence: 92%
“…This begs the question: how could the later, better models fail to simulate the causal connection reported with the earlier, simpler models? A resolution to this conundrum was recently proposed by Polvani et al (2019), hereafter PBS19, who showed that much of the earlier literature had failed to properly account for the large internal variability associated with the stratospheric polar vortex and with the NAO. Focusing primarily on the 199 Pinatubo eruption, PBS19 analyzed three "large ensembles" of model runs, and showed how tiny initial perturbations of the same model forced with the same volcanic aerosols result vastly different winter temperature anomalies over Eurasia.…”
Section: Introductionmentioning
confidence: 99%
“…Impact of stratospheric heating on tropospheric and surface climate High for certain aerosol choices, such as sulfate; stratospheric-heating effects on tropospheric and surface climate are known but uncertainties regarding magnitude of responses and robustness across models 6,47,168 High; stratospheric heating may be responsible for many of the surface-climate side effects of SAG 47…”
Section: Responsementioning
confidence: 99%